2016
DOI: 10.1002/hbm.23407
|View full text |Cite
|
Sign up to set email alerts
|

Brain reward system's alterations in response to food and monetary stimuli in overweight and obese individuals

Abstract: The brain's reward system is crucial to understand obesity in modern society, as increased neural responsivity to reward can fuel the unhealthy food choices that are driving the growing obesity epidemic. Brain's reward system responsivity to food and monetary rewards in individuals with excessive weight (overweight and obese) versus normal weight controls, along with the relationship between this responsivity and body mass index (BMI) were tested. The sample comprised 21 adults with obesity (BMI > 30), 21 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 45 publications
2
50
1
Order By: Relevance
“…Given its complexity, its activity is closely associated to that of other main networks, such as the salience network, the emotional arousal network and the executive network (Gupta et al, 2015 ). Brain structural and functional connectivity changes in the reward system, closely resembling those observed in addiction (Michaud et al, 2017 ), have also been reported in obesity (Marqués-Iturria et al, 2015 ; Blechert et al, 2016 ; Carnell et al, 2017 ; Papageorgiou et al, 2017 ; Verdejo-Román et al, 2017 ), affecting several tracts (e.g., the anterior thalamic radiation, accumbofrontal fasciculus, forceps minor (FMi), cingulum, superior longitudinal fasciculus, inferior fronto-occipital fasciculus (Cho et al, 2013 ; Marqués-Iturria et al, 2015 ; Kullmann et al, 2016 ; Nangunoori et al, 2016 ; Papageorgiou et al, 2017 )) of the reward pathway (Sesack and Grace, 2010 ; Xu et al, 2012 ; Bracht et al, 2015 ; Yang et al, 2017 ). Only few studies, however, have investigated whether structural connectivity might be disrupted in people with genetic risk for obesity (Dennis et al, 2014 ; Spieker et al, 2015 ), reporting somewhat conflicting results.…”
Section: Introductionmentioning
confidence: 67%
“…Given its complexity, its activity is closely associated to that of other main networks, such as the salience network, the emotional arousal network and the executive network (Gupta et al, 2015 ). Brain structural and functional connectivity changes in the reward system, closely resembling those observed in addiction (Michaud et al, 2017 ), have also been reported in obesity (Marqués-Iturria et al, 2015 ; Blechert et al, 2016 ; Carnell et al, 2017 ; Papageorgiou et al, 2017 ; Verdejo-Román et al, 2017 ), affecting several tracts (e.g., the anterior thalamic radiation, accumbofrontal fasciculus, forceps minor (FMi), cingulum, superior longitudinal fasciculus, inferior fronto-occipital fasciculus (Cho et al, 2013 ; Marqués-Iturria et al, 2015 ; Kullmann et al, 2016 ; Nangunoori et al, 2016 ; Papageorgiou et al, 2017 )) of the reward pathway (Sesack and Grace, 2010 ; Xu et al, 2012 ; Bracht et al, 2015 ; Yang et al, 2017 ). Only few studies, however, have investigated whether structural connectivity might be disrupted in people with genetic risk for obesity (Dennis et al, 2014 ; Spieker et al, 2015 ), reporting somewhat conflicting results.…”
Section: Introductionmentioning
confidence: 67%
“…We used a two-sample t-test to investigate whether there were any between-group differences between priming conditions. Previous studies showed quadratic associations of responsivity to reward and the physiology of the reward system with BMI 20 , 39 42 . We therefore tested whether the cumulative priming effect was related to BMI 2 .…”
Section: Methodsmentioning
confidence: 93%
“…Food often comes at a cost, which requires weighing your options. Obese individuals may be less willing to, first, pay money for plain than highly palatable food items [73]; second, exert effort to obtain food or monetary rewards [66,166]; and third, wait for a larger reward if a smaller immediate reward is offered simultaneously, as consistently observed in delay discounting tasks ( [167][168][169][170], but see [51•]). Willingness to exert effort relies on regions in the affective loop and is particularly interesting because of its link to dopamine [171,172] as well as lowgrade systemic inflammation [173], which is highly prevalent in obesity (see Box 1).…”
Section: Self-control and Cost-benefit Decision-makingmentioning
confidence: 99%